(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Cucumbers (Cucumis sativus) are highly perishable and often suffer significant postharvest losses. Chlorinated water and modified atmosphere packaging (MAP) are used to reduce microbial load, delay spoilage, lower respiration rates, and oxidative stress. However, limited research has examined the combined effects of washing using filtered water, blanching at specific temperatures (25 °C and 45 °C), cutting techniques, and vacuum packaging on cucumber quality. Therefore, the objectives of this study are: (1) to determine the effects of different washing solutions and blanching on moisture content, colour, and texture of fresh local cucumbers; (2) to evaluate the impact of various cutting techniques on the physicochemical properties and texture of selected cucumbers; and (3) to identify the effects of selected washing, blanching, cutting technique with vacuum packaging at various storage conditions on shelf life of cucumbers. Blanching at 25 °C with filtered water (FW25) significantly increased cucumber hardness (704.5±38.7 N) and maintained optimal moisture content (96.8±0.4%). Cylindrical cuts treated with FW25 (C25) exhibited higher firmness (530.9 g·sec) compared to non-treated cuts (CC) (494.50 g·sec), likely due to better structural integrity of C25. The C25 kept in vacuum packaging effectively inhibited microbial growth after six days of storage (VT6) compared to unpackaged samples (NC6) (2.9×10-3 log CFU/g) due to an anaerobic environment in vacuum packaging, which limits oxygen availability and suppresses microbial proliferation. This study offers valuable insights for optimizing postharvest handling of cucumbers to meet consumer demand for fresh, nutritious produce.